DIFFERENCES IN MOTIVATION AND STUDENT LEARNING OUTCOMES LEARNED WITH DIGITAL SNAKES AND LADDERS MEDIA ON CHEMICAL BONDING MATERIALS AT SMAN 5 MEDAN - Jannah, Nazria Marwatul; Zubir, Moondra (Universitas Lampung, 2024)
Research purposes This that is For know difference motivation and results Study students studied with snake media digital ladder on material bond chemistry as well as enhancement and correlation between motivation and results Study student . Study This is study quantitative . Deep sample study This taken purposive sampling of 2 classes i.e. X 11 as class experiments I and X 10 as class experiment II, where each class 30 students were taken based on similarity results pretest . Instruments used that is instrument test form question choice double as well as non- test instrument form sheet questionnaire motivation learn . Testing hypothesis done with using the SPSS Statistics version 24 for Windows computer program Independent Sample T-Test and Bivariate Pearson Correlation. For hypothesis I is obtained sig value . (2-tailed) 0.000 (0.05 ) so that H a accepted , which means there is difference motivation Study students studied with snake media digital ladder . For hypothesis II is obtained mark sig. (2-tailed) 0.022 (0.05 ) so that H a accepted , which means there is difference results Study students studied with snake media digital ladder . For hypothesis III is obtained enhancement motivation learn what is learned with snake media digital ladder by 40%. For hypothesis IV is obtained enhancement results learn what is learned with snake media the digital ladder is 76% in the category tall . For hypothesis V is obtained mark sig. (2-tailed) of 0,000 (0.05) so that H a accepted , which means there is correlation between motivation learning and results Study students studied with snake media digital ladder on material bond chemistry .Keywords : Digital Snakes and Ladders , Motivation Learning , Learning Results , Chemical Bonding DOI: 10.23960/jppk.v13i2.30012